Introducing the Program for Climate-Smart Livestock - Ericksen, Polly J. (International Livestock Research Institute, 2020)
Polly Ericksen introduces the Program for Climate-Smart Livestock (PCSL), which supports key actors in the livestock sector in Ethiopia, Kenya and Uganda to include climate change adaptation and mitigation in their farming practices, sector strategies and investment projects. The project is financed and coordinated by the German Corporation for International Cooperation GmbH (GIZ), commissioned by the Government of the Federal Republic of Germany.